Is China climbing up the quality ladder? - Gabor Pula; Daniel Santabárbara (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
There is an ongoing debate in the literature about the quality content of Chinese exports and to what extent China imposes a threat to the market positions of advanced economies. While China's export structure is very similar to that of the advanced world, its export unit values are well below the level of developed economies. Building on the assumption that unit values reflect quality the prevailing view of the literature is that China exports low quality varieties of the same products than its advanced competitors. This paper challenges this view by relaxing the assumption that unit values reflect quality. We derive the quality of Chinese exports to the European Union by estimating disaggregated demand functions from a discrete choice model. The paper has three major findings. First, China's share on the European Union market is larger than would be justified only by its low average prices, implying that the quality of Chinese exports is high compared to many competitors. Second, China has gained quality relative to other competitors since 1995, indicating that China is climbing up the quality ladder. Finally, our analysis on the supply side determinants reveals that the relatively high quality of Chinese exports is related to processing trade and the increasing role of global production networks in China.
URN:NBN:fi:bof-201408072093
Keywords: F12; F14; F15; F23; 330; Chinese exports; vertical product differentiation; quality ladder; global production networks; discrete choice model; COMEXT database